Governing Global South–North Organic Food Exporting: Possibilities for Democratic Engagement and Impacts for Smallholder Farmers - Lyons, Kristen (The International Journal of Sociology of Agriculture and Food, 2013)
Export of certified organic agricultural products is one of a number of market-based development strategies for improving the socio-economic and ecological realities of smallholders in the Global South. Yet the outcomes of participation in these export-led initiatives have been mixed. The extent to which organic export agriculture might deliver benefits to smallholders is, at least in part, related to the deliberative capacity of organic governance processes – on which participation in organic exporting relies. Deliberative capacity is taken to include broadly inclusive and authentic inclusion of smallholders, and other local actors, in organic governance processes. This article contributes to understandings of participation in organic governance and its outcomes by evaluating smallholder and other Southern actor engagement in three aspects of organic governance arrangements: organic standards, compliance and inspection requirements. The results presented here – drawing from fieldwork in Uganda and Ghana – demonstrate that, on the one hand, organic governance arrangements are characterized by limited democratic engagement and decision-making; standard-setting processes largely exclude smallholder and other Southern actor interests, as well as creating new forms of dependency between smallholders and export companies. However, and in other circumstances, the introduction of group certification and local inspection services has provided smallholders with bargaining power with export companies and northern buyers. These spaces point to possibilities for organic governance to improve the socio-economic and ecological realities of smallholders in the Global South.